2014
DOI: 10.1371/journal.pntd.0002786
|View full text |Cite
|
Sign up to set email alerts
|

Combined Inflammatory and Metabolic Defects Reflected by Reduced Serum Protein Levels in Patients with Buruli Ulcer Disease

Abstract: Buruli ulcer is a skin disease caused by Mycobacterium ulcerans that is spreading in tropical countries, with major public health and economic implications in West Africa. Multi-analyte profiling of serum proteins in patients and endemic controls revealed that Buruli ulcer disease down-regulates the circulating levels of a large array of inflammatory mediators, without impacting on the leukocyte composition of peripheral blood. Notably, several proteins contributing to acute phase reaction, lipid metabolism, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 37 publications
4
21
2
Order By: Relevance
“…All lesions were culture positive until 2 weeks but thereafter all were culture negative . Some follow‐up studies have indicated that healing delay may occur in up to two‐thirds of patients within 25 weeks from the start of SR treatment . Sarfo et al.…”
Section: Prolong Viability Of Mu In Bu Lesionsmentioning
confidence: 98%
See 1 more Smart Citation
“…All lesions were culture positive until 2 weeks but thereafter all were culture negative . Some follow‐up studies have indicated that healing delay may occur in up to two‐thirds of patients within 25 weeks from the start of SR treatment . Sarfo et al.…”
Section: Prolong Viability Of Mu In Bu Lesionsmentioning
confidence: 98%
“…Philips et al. subsequently reported that BU patients with active ulcers showed distinctive profile of immune suppression marked by down modulation of selected cytokines and an impaired capacity to produce Th1, Th2, and Th17 cytokines when stimulated with mitogenic agents . Immunohistopathological studies of lesions from BU patients after SR regimen have demonstrated treatment‐associated initiation of vigorous immune responses and the development of ectopic lymphoid tissue in the BU lesions .…”
Section: Immune Suppression Associated With Bu Diseasementioning
confidence: 99%
“…Multi‐analyte profiling of PHA‐stimulated whole blood culture supernatants revealed that in fact, most T cell‐derived cytokines were suppressed during disease progression [Phillips et al., ]. Moreover, patients with BU displayed a distinctive proteomic signature in their serum, marked by a down‐regulation of multiple mediators of inflammation [Phillips et al., , ]. The immunosuppressive signature of BU persisted weeks after completion of antibiotic therapy in treated individuals [Phillips et al., , ], thus correlating with the continued presence of mycolactone.…”
Section: Buruli Ulcer the Third Most Common Mycobacterial Diseasementioning
confidence: 99%
“…In addition to a lack of inflammatory infiltrates at the level of skin lesions (7), patients with BU display systemic alterations in their cellular immune responses, evidenced by an impaired capacity of T cells to produce cytokines ex vivo upon stimulation with mitogenic agents (8)(9)(10). Contrary to wild-type strains, mycolactone-deficient mutants of M. ulcerans do not impair the capacity of T cells to produce interleukin-2 (IL-2) in animal models, showing that mycolactone is the cause of these cellular response defects (11).…”
Section: Introductionmentioning
confidence: 99%